Dynamic Forecasting of Government Foreign Debt: Case of Indonesia - Yozi Aulia Rahman; Amin Pujiati (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
This study aims to forecast the value of the Indonesian government foreign debt in 2020-2024. The secondary data of time series during the period of 2010-2019 on Indonesian government foreign debt are used as the basis of forecasting for the next five years by using ARIMA (Autogressive Integrated Moving Average). The results show that the selected ARIMA models for forecasting are ARIMA (3,1,3) after the unit root test is carried out and 16 ARIMA models are tested. The value of government foreign debt is predicted to keep increasing from 2020 to 2024 amounted to USD 253.01. Then, compared to government debt in January 2010, within 11 years, government foreignÃ‚Â  debt is predicted to rise by 169.6%.